Cardiovascular risk factor burden and association with CKD in Ghana and Nigeria (2023)
Introduction: Cardiovascular disease is the leading cause of morbidity and mortality in patients with chronic kidney disease (CKD); however, the burden of cardiovascular risk factors in patients with CKD in Africa is not well characterized. We determined the prevalence of selected cardiovascular risk factors, and association with CKD in the Human Heredity for Health in Africa Kidney Disease Research Network study. Methods: We recruited patients with and without CKD in Ghana and Nigeria. CKD was defined as estimated glomerular filtration rate of <60 ml/min per 1.73 m2 and/or albuminuria as albumin-to-creatinine ratio <3.0 mg/mmol (<30 mg/g) for $3 months. We assessed self-reported (physician-diagnosis and/or use of medication) hypertension, diabetes, and elevated cholesterol; and self-reported smoking as cardiovascular risk factors. Association between the risk factors and CKD was determined by multivariate logistic regression. Results: We enrolled 8396 participants (cases with CKD, 3956), with 56% females. The mean age (45.5 _ 15.1 years) did not differ between patients and control group. The prevalence of hypertension (59%), diabetes (20%), and elevated cholesterol (9.9%), was higher in CKD patients than in the control participants (P < 0.001). Prevalence of risk factors was higher in Ghana than in Nigeria. Hypertension (adjusted odds ratio [aOR] ¼ 1.69 [1.43–2.01, P < 0.001]), elevated cholesterol (aOR ¼ 2.0 [1.39–2.86, P < 0.001]), age >50 years, and body mass index (BMI) <18.5 kg/m2 were independently associated with CKD. The association of diabetes and smoking with CKD was modified by other risk factors. Conclusion: Cardiovascular risk factors are prevalent in middle-aged adult patients with CKD in Ghana and Nigeria, with higher proportions in Ghana than in Nigeria. Hypertension, elevated cholesterol, and underweight were independently associated with CKD.